2017
DOI: 10.4088/jcp.16r11113
|View full text |Cite
|
Sign up to set email alerts
|

<em>S</em>-Adenosylmethionine (SAMe) for Neuropsychiatric Disorders

Abstract: Objective A systematic review on S-adenosylmethionine (SAMe) for treatment of neuropsychiatric conditions and co-morbid medical conditions. Data Sources Searches were conducted between 7/15/2015 and 9/28/2016 by combining search terms for SAMe (s-adenosyl methionine or s-adenosyl-l-methionine) with terms for relevant disease states including (major depressive disorder, MDD, depression, perinatal depression, human immunodeficiency virus, HIV, Parkinson's, Alzheimer's, dementia, anxiety, Schizophrenia, psychot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(57 citation statements)
references
References 106 publications
(102 reference statements)
0
54
2
1
Order By: Relevance
“…In children, plasma norepinephrine levels were correlated with inefficient conditioned pain modulation response (44). Furthermore, norepinephrine is increased by S-Adenosyl-Methionine (SAMe), which is the primary methyl group donor for several metabolic compounds and cysteine (DNA) methylation (45). SAMe is believed to have a positive influence on multiple neuropsychiatric disorders and due to its role in increasing catechol-O-methyltransferase (COMT) activity, SAMe has been suggested to reduce aggressive behavior in psychiatric patients (45,46).…”
Section: Serotonergic Dopaminergic and Gabaergic Pathways And Childmentioning
confidence: 99%
“…In children, plasma norepinephrine levels were correlated with inefficient conditioned pain modulation response (44). Furthermore, norepinephrine is increased by S-Adenosyl-Methionine (SAMe), which is the primary methyl group donor for several metabolic compounds and cysteine (DNA) methylation (45). SAMe is believed to have a positive influence on multiple neuropsychiatric disorders and due to its role in increasing catechol-O-methyltransferase (COMT) activity, SAMe has been suggested to reduce aggressive behavior in psychiatric patients (45,46).…”
Section: Serotonergic Dopaminergic and Gabaergic Pathways And Childmentioning
confidence: 99%
“…Although SSRIs did not prove effective in the treatment of fatigue in PBC in a small randomized study [29], antidepressants are frequently prescribed in fatigued patients with PBC [30]. A recent review strongly suggested that SAMe might prove useful in various psychiatric conditions including not only depression but also mood disturbance or anxiety [31]. In our patients treated with SAMe we observed a significant improvement in the STAI 2 questionnaire, which is a well validated tool for the assessment of anxiety.…”
Section: Discussionmentioning
confidence: 61%
“…SAM, either as drug or nutritional supplement, is widely used for the treatment of liver diseases, depression and ostheoarthtitis, with high tolerability and the very few side effects [ 47 ] limited to mild gastrointestinal upsets, usually resolved after lowering doses. Oral formulations, in the form of coated gastroresistant tablets and capsules, allow SAM irritating activity on the gastric mucosa to be overcome, also hiding its unpleasant taste.…”
Section: Discussionmentioning
confidence: 99%